Novel CO2 philic surfactants for CO2 mobility control for enhanced oil recovery applications - Sagir, M. (Society of Petroleum Engineers, 2014)
The CO2 injection for mobilization of trapped oil in porous media is the most frequently applied method for EOR projects. Despite of the fact that the CO2 injection can effectively produce the trapped oil, many problems such as viscous fingering, gravity override, high ratio of COP2 to oil produced and early breakthrough are required to be resolved. These challenges can effectively be reduced by employing CO 2 philic surfactants, which have exhibited more practical advantages over conventional surfactants. A study has been conducted to develop and evaluate CO2 philic surfactants for the Co2 mobility control for EOR applications.Interfecial tention (IFT) between CO2 and surfactant solution was measured. In addition, coreflood experiments were conducted for mobility reduction factor (MRF) measurements. It was observed that the IFT appreciably decreased by using the surfactant in 1 concentration. MRF from coreflood results was found 2.3. This showed that as compared to conventional surfactants, newly developed CO2 philic surfactants significantly reduce the mobility of the injected CO2. Copyright 2014 , Society of Petroleum Engineers.